Impact of English academic reading strategies and proficiency on academic performance: a study of Malaysian Public University Foundation Students - Chelster Sherralyn Jeoffrey Pudin; John Mark Storey; Loh, Yoke Len; Suyansah Swanto; Wardatul Akmam Din; Norazah Mohd Suki (Solid State Technology, 2020)
One of the ways to help students’ transition into their degree programme of choice in the university is through foundation programs. In the foundation program, apart from critical thinking and communication skills, students are seen lacking in language proficiency especially in English language. Reading academic materials has been identified to be one of the main challenges faced by the students in learning the English language. Therefore, students need to be equipped with a range of reading strategies as they attempt to process written information as this will help them to outdo the challenges. This paper aims to determine the effective reading strategies used by students of different MUET bands that are required for comprehending academic texts and the impact of these strategies on the students’ academic performance. SEM was employed to test the postulated relationships among the MUET test performance and the use of reading strategies.of 120 foundation students. The findings reveal that there are statistically significant relationships existed between academic performance and use of reading strategies. Cognitive- based reading strategies (UYMP, CMK, and RME) as well as strategies in managing one’s reading progress (OEYL) are more frequently employed than strategies in managing one’s emotions (MYE) and learning from others (LO). The identification of effective reading strategies may pave the way for improvement of reading skills among ESL students. Instructors can provide students with practice in utilising these strategies. The establishment of the correlation of target language knowledge and reading strategies with reading performance will be able to shed some light on how language instructors can facilitate students in reading academic texts thus narrowing the 1 gap between proficient and less proficient readers. The findings will inform instructors on how to guide students in comprehending academic texts.